Can savannas become forests? A coupled analysis of nutrient stocks and fire thresholds in central Brazil - Silva, Lucas C.R.; Hoffmann, William A.; Rossatto, Davi R. [UNESP]; Haridasan, Mundayatan; Franco, Augusto C.; Horwath, William R. (Springer Nature, 2013)
Aims: The effects of fire ensure that large areas of the seasonal tropics are maintained as savannas. The advance of forests into these areas depends on shifts in species composition and the presence of sufficient nutrients. Predicting such transitions, however, is difficult due to a poor understanding of the nutrient stocks required for different combinations of species to resist and suppress fires. Methods: We compare the amounts of nutrients required by congeneric savanna and forest trees to reach two thresholds of establishment and maintenance: that of fire resistance, after which individual trees are large enough to survive fires, and that of fire suppression, after which the collective tree canopy is dense enough to minimize understory growth, thereby arresting the spread of fire. We further calculate the arboreal and soil nutrient stocks of savannas, to determine if these are sufficient to support the expansion of forests following initial establishment. Results: Forest species require a larger nutrient supply to resist fires than savanna species, which are better able to reach a fire-resistant size under nutrient limitation. However, forest species require a lower nutrient supply to attain closed canopies and suppress fires; therefore, the ingression of forest trees into savannas facilitates the transition to forest. Savannas have sufficient N, K, and Mg, but require additional P and Ca to build high-biomass forests and allow full forest expansion following establishment. Conclusions: Tradeoffs between nutrient requirements and adaptations to fire reinforce savanna and forest as alternate stable states, explaining the long-term persistence of vegetation mosaics in the seasonal tropics. Low-fertility limits the advance of forests into savannas, but the ingression of forest species favors the formation of non-flammable states, increasing fertility and promoting forest expansion. © 2013 Springer Science+Business Media Dordrecht.
Keywords: Cerrado; Ecosystem dynamics; Fire; Forest expansion; Nutrient cycling; Soil-plant interactions; Succession; Tradeoffs; Tropics